A tale of two gorges: Late Quaternary site formation and surface dynamics in the Mula basin (Murcia, Spain) - Angelucci, Diego E. (2019)
We present a case-study in Palaeolithic archaeology focusing on formation processes at cave- and rockshelter-sites in a Mediterranean context and on the correlation between site deposits, Quaternary surfacesediments and the morphology of the surrounding land.We study three sites located in the basin of RiverMula (Murcia, Spain): the cave-site of Cueva Ant on and the rock-shelters of Finca Doña Martina and Abrigo de la Boja, in the Rambla Perea valley. They are examined through an integrated geoarchaeological approach that takes into account geomorphological, stratigraphic and soil micromorphological data. The three sites are found within a short distance and cover similar time spans within the Upper Pleistocene but have different formations and show distinct degrees of preservation of the archaeological record. Cueva Antón features a densely-stratified, mostly alluvial succession, with excellent preservation of stratigraphic layout and sedimentary facies. The succession represents a well-preserved record of past activity of the River Mula and can be correlated to its open-air alluvial system. The Rambla Perea sites, despite their immediate vicinity, underwent distinct formation dynamics, with a complex interaction among the site deposits and the hillslope along which they are found, and exhibit different degrees of preservation of archaeological layers and features.We summarise the evidence from these sites and then discuss its implications for site formation, for the preservation of the archaeological record and for the correlation between the ‘inside’ (the archaeological successions preserved within caves and in rockshelters) and the ‘outside’ (the geomorphological setting of the land and the evolution of Quaternary surface dynamics through time).